Instrumental Case In Turkish Language - Ipek, Birol (Selcuk Univ, Inst Turkish Studies, 2008)
In Turkish, instrument case affix was n in the ancient Turkish language. After this affix was abolished from usage, ile and birle particles come into usage. The instrument affix which was used in ancient Turkish language, lives in Turkish of Turkey as a prasal ending in a few words. This affix that was used very often in the past, lost its usage over time. It is used only in structure of some words. Sometimes n forms a situation called compile of ending by coming after particle of ile. That a particle and an ending which is close to it as regarts to function comprises is an event seen very often. This work absorbs all the terms from old Turkish to Turkish of Turkey. Inview of the wholeness of the subject, dialects of Turkish and regional accents of Modern Turkish were included to this work. In each part of this work, instrument affix, particles used in this function were examined one by one and instrumental affix were assessed as a whole.
Keywords: Turkish Language; Affix; Case Affix; Instrument Case Affix